Blended-learning pain neuroscience education and exercise in high school students with chronic neck pain: a randomized controlled trial - Andias, Rosa (2022)
Pain neuroscience education (PNE) and exercise have emerged as potential interventions in adolescents with chronic pain; however, very few studies have explored their effectiveness. Blended-learning approaches combining face-to-face and online educational sessions have also emerged as facilitating methods of health education. This study aimed to compare the effectiveness of exercises and PNE versus exercise alone in adolescents with chronic neck pain (NP).